2014
DOI: 10.1128/aac.02738-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-Resistant TEM- and OXA-1-Producing Escherichia coli Isolates Resistant to Amoxicillin-Clavulanate Are More Clonal and Possess Lower Virulence Gene Content than Susceptible Clinical Isolates

Abstract: In a previous prospective multicenter study in Spain, we found that OXA-1 and inhibitor-resistant TEM (IRT) ␤-lactamases constitute the most common plasmid-borne mechanisms of genuine amoxicillin-clavulanate (AMC) resistance in Escherichia coli. In the present study, we investigated the population structure and virulence traits of clinical AMC-resistant E. coli strains expressing OXA-1 or IRT and compared these traits to those in a control group of clinical AMC-susceptible E. coli isolates. All OXA-1-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…Among the 257 AMC-resistant E. coli, all 5 isolates (1.9%) resistant to amikacin contained the aac(6 )-Ib gene. Although it has been described that the aac(6 )-Ib gene confers resistance to amikacin, kanamycin, tobramycin and netilmicin [7], when applying EUCAST (2) To (2) K, To (2) Gm (1) To (1) K (1) Susceptible (1) aph (3 )-Ia 21 (20.0) K, Nm As expected (20) As expected (20) Gm, K, Nm (1) Gm, K (1) aac(3)-IIa 9 (8.6) Gm, Nt, To As expected (8) As expected (2) Gm, K, Nt, To (1) Gm, To (2) Gm (5) aac (6 )-Ib, aac(3)-IIa 8 (7.6) Ak, Gm, K, Nt, To As expected (1) As expected (1) Gm, K, Nt, To (7) Gm, K, Nt, To (2) Gm, K, To (4) Gm, To (1) aac (3) breakpoints only 4 of the 25 isolates (16%) containing only the aac(6 )-Ib gene presented this specific pattern, whilst the remaining 21 isolates were resistant to one or more of gentamicin, tobramycin, netilmicin or kanamycin, but not to amikacin. Using breakpoints established by the CLSI, none of isolates carrying the aac(6 )-Ib gene had the expected resistance phenotype to aminoglycosides; in fact, this gene was detected in one strain susceptible to all tested aminoglycosides ( Table 2).…”
Section: Molecular Characterisation Of Mechanisms Of Resistance To Ammentioning
confidence: 65%
See 2 more Smart Citations
“…Among the 257 AMC-resistant E. coli, all 5 isolates (1.9%) resistant to amikacin contained the aac(6 )-Ib gene. Although it has been described that the aac(6 )-Ib gene confers resistance to amikacin, kanamycin, tobramycin and netilmicin [7], when applying EUCAST (2) To (2) K, To (2) Gm (1) To (1) K (1) Susceptible (1) aph (3 )-Ia 21 (20.0) K, Nm As expected (20) As expected (20) Gm, K, Nm (1) Gm, K (1) aac(3)-IIa 9 (8.6) Gm, Nt, To As expected (8) As expected (2) Gm, K, Nt, To (1) Gm, To (2) Gm (5) aac (6 )-Ib, aac(3)-IIa 8 (7.6) Ak, Gm, K, Nt, To As expected (1) As expected (1) Gm, K, Nt, To (7) Gm, K, Nt, To (2) Gm, K, To (4) Gm, To (1) aac (3) breakpoints only 4 of the 25 isolates (16%) containing only the aac(6 )-Ib gene presented this specific pattern, whilst the remaining 21 isolates were resistant to one or more of gentamicin, tobramycin, netilmicin or kanamycin, but not to amikacin. Using breakpoints established by the CLSI, none of isolates carrying the aac(6 )-Ib gene had the expected resistance phenotype to aminoglycosides; in fact, this gene was detected in one strain susceptible to all tested aminoglycosides ( Table 2).…”
Section: Molecular Characterisation Of Mechanisms Of Resistance To Ammentioning
confidence: 65%
“…We also found that 23 of 25 strains producing CTX-M-15 had the aac(6 )-Ib-cr gene, of which 69.5% belonged to clonal complex ST131 and 30.5% were ST23 or ST10 [20]. On the other hand, it is also remarkable that 5 of 11 isolates hyperproducing chromosomal AmpC harboured the aac(6 )-Ib gene, in contrast with the results of Lindemann et al [12] who did not find aac(6 )-Ib in any of isolates with AmpC hyperproduction.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The bla CMY-2 isolates from two sampling sites showed ESBL, AmpC and PMQR E. coli from American crows 2031 significant clonal similarity with dominance of ST88 and ST336 in California and ST48 and ST345 in New York, indicating their common source. ST88 has been described as both extraintestinal pathogenic E. coli (ExPEC) and avian pathogenic E. coli (APEC) (Maluta et al, 2014) and betalactamase-producing isolates of this clonal group have been reported in hospitals in France (Cremet et al, 2010) and Spain (Oteo et al, 2014) as well as from cases of bovine mastitis in the UK (Timofte et al, 2014). ST345 has been reported as APEC (Maluta et al, 2014) and the isolates of this ST have been found in wild birds in Europe (Jamborova et al, 2015), companion animals (Poirel et al, 2013) and human clinical samples in Asia (Yuan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…coli strains were screened for the presence of 49 virulence factors (including 19 adhesins, 4 siderophores, 11 toxins, 6 capsule synthesis-associated genes, and 9 miscellaneous genes). Screening was performed by multiplex PCRs according to previously reported methodology [23]. In the case of K .…”
Section: Methodsmentioning
confidence: 99%